Equity and adequacy of international donor assistance for global malaria control: an analysis of populations at risk and external funding commitments. - Snow, R; Okiro, E; Gething, P; Atun, R; Hay, S (Elsevier, 2010)
BACKGROUND: Financing for malaria control has increased as part of international commitments to achieve the Millennium Development Goals (MDGs). We aimed to identify the unmet financial needs that would be biologically and economically equitable and would increase the chances of reaching worldwide malaria-control ambitions. METHODS: Populations at risk of stable Plasmodium falciparum or Plasmodium vivax transmission were calculated for 2007 and 2009 for 93 malaria-endemic countries to measure biological need. National per-person gross domestic product (GDP) was used to define economic need. An analysis of external donor assistance for malaria control was done for the period 2002-09 to compute overall and annualised per-person at-risk-funding commitments. Annualised malaria donor assistance was compared with independent predictions of funding needed to reach international targets of 80% coverage of best practices in case-management and effective disease prevention. Countries were ranked in relation to biological, economic, and unmet needs to examine equity and adequacy of support by 2010. FINDINGS: International financing for malaria control has increased by 166% (from $0·73 billion to $1·94 billion) since 2007 and is broadly consistent with biological needs. African countries have become major recipients of external assistance; however, countries where P vivax continues to pose threats to control ambitions are not as well funded. 21 countries have reached adequate assistance to provide a comprehensive suite of interventions by 2009, including 12 countries in Africa. However, this assistance was inadequate for 50 countries representing 61% of the worldwide population at risk of malaria-including ten countries in Africa and five in Asia that coincidentally are some of the poorest countries. Approval of donor funding for malaria control does not correlate with GDP. INTERPRETATION: Funding for malaria control worldwide is 60% lower than the US$4·9 billion needed for comprehensive control in 2010; this includes funding shortfalls for a wide range of countries with different numbers of people at risk and different levels of domestic income. More efficient targeting of financial resources against biological need and national income should create a more equitable investment portfolio that with increased commitments will guarantee sustained financing of control in countries most at risk and least able to support themselves. FUNDING: Wellcome Trust.